Pengelolaan Usaha Kesehatan Sekolah Di SMP Negeri 1 Ngadirojo Pacitan - SUTADI, Sutadi; , Dr. Samino, M.M; , Dr. Sabar Narimo, M.M., M.Pd (2015)
This target Research is descripe ( 1) Planning of UKS Junior High School 1 of Ngadirojo Pacitan ( 2) Execution of UKS ( 3) Observation and of assessment UKS; ( 4) Role of teacher in management of UKS ( 5) Role of educative participant in realizing UKS. This type Research is qualitative with an ethnography design. The main Subject of research is headmaster, teacher and student SMP Negeri 1 Ngadirojo Pacitan. Technique Interview use circumstantial interview, observation, and documentation study. Data analysis conducted with data collecting, data discount, presentation of data, and withdrawal of verification or conclusion. The validity of data using technique data source triangulation and method triangulation. Result of this Research indicate that ( 1) Planning of management of UKS SMP Negeri 1 Ngadirojo started planned TEAM executor of UKS, later; then plan program activity of UKS, room of UKS, and medium and also tools which room of UKS. ( 2) Execution of UKS SMP Negeri 1 Ngadirojo have been focused execution Three fundamental program (Trias UKS). ( 3) Form observation and assessment of UKS SMP Negeri 1 Ngadirojo Sub-Province of Pacitan done by have coordination with Team and Puskesmas Builder of UKS District. ( 4) Role of teacher of SMP Negeri 1 Ngadirojo in management of UKS SMP Negeri 1 Ngadirojo is as planner of program activity of UKS and as executor of program of UKS. Teacher of SMP Negeri 1 Ngadirojo follow to participate to evaluate program of UKS. Teacher of SMP Negeri 1 Ngadirojo also participate to motivate student to always to keep cleaning and health of them. ( 5) Role of educative participant in this UKS there is two role, that is as party becoming goals execution of UKS, and as cadre of UKS. Role of educative participant as party becoming especial goals of execution of UKS is to execute hygiene programs and health which have been planned by TEAM Executor Of UKS SMP Negeri 1 Ngadirojo. Role of student of SMP Negeri 1 Ngadirojo when becoming KKR is following to assist execution of activity of UKS like assisting to manage room of UKS, keep cleaning it, in turn to guard UKS, and also helping sick student.